An Empirical Review of Indigenous Knowledge System from Management Perspective - Khatri, Rupesh (Journal of Entrepreneurship & Management Studies, 2025)
The study aims to explore the significance of Indigenous Knowledge (IK) from a management perspective. It emphasized role of IK in sustainable development, governance, and innovation. It analyzed key IK components in education, research, and industry practices. The study emphasized potential use of IK in modern applications and global recognition. The study focused on policy interventions for the preservation and integration of IK into academic and organizational frameworks. The study used an empirical review methodology to examine the role of Indigenous Knowledge across various domains such as leadership, agriculture, and climate change adaptation. The findings of the study include the researcher identified key themes and evaluated the relevance and impact of Indigenous practices. The study adopted a descriptive research design to provide a comprehensive understanding. It also emphasizes gaps in existing literature for future research. The study underlined use of IK for promoting local development, sustainability, and flexibility, through practices like agro ecology and sustainable resource management. It emphasized to integrate Indigenous governance systems into modern frameworks and the need for preserving IK through documentation and community-driven efforts. The study highlights the significance of aligning IK with modern technology, policies, and intellectual property protections to enhance its impact and safeguard it for future generations. The study concluded that, integration of Indigenous Knowledge (IK) into management practices can enhance decision making, leadership, sustainability, ethical and inclusive business practices. The study suggested to formalize and protect IK through legal frameworks and policy interventions to ensure fair compensation, preserve cultural heritage, and support sustainable development aligned with global goals.